Strategies for Protection and Recovery of Domestic Violence Victims: Analysis of Rumah Putro's Role for Women and Children: Perlindungan dan Pemulihan Korban KDRT: Analisis Peran Rumah Putro terhadap Perempuan dan Anak - Abdullah, Muslem (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
This study examines the protection and recovery strategies for victims of domestic violence (KDRT) at Rumah Putro Banda Aceh, which serves as a center for data, services, empowerment, and cross-sector coordination. Its primary goal is to achieve gender equality and justice by optimizing referral services and protection mechanisms for women and children victims of physical and psychological abuse. The main challenge faced is the lack of standardization of Rumah Putro as a safe house for KDRT victims. This research employs qualitative methods with a field approach to understand and investigate community issues in a naturalistic manner. The findings reveal that Rumah Putro has made various efforts to prevent domestic violence in Aceh. In carrying out its functions, Rumah Putro collaborates with hospitals for medical needs and with the psychology association at Ar-Raniry State Islamic University Banda Aceh for the psychological, mental, and trauma recovery of victims. The forms of protection provided by Rumah Putro include: 1) Provision of temporary shelters or safe houses; 2) Legal assistance; and 3) Psychological recovery. This study provides a comprehensive overview of the effectiveness of the protection and recovery efforts conducted by Rumah Putro and identifies obstacles and potential improvements that can be implemented to enhance services for women and children victims of domestic violence.